Crossing the border from a CALL lab to the real world: a material databank for and by teacher-trainees - Puteh, Fatimah (Penerbit UTM Press, 2009)
Kelly (1996) maintains that a teacher needs a great deal of information in order to function well in his/her profession. The expectation of a teacher is so high that many are unable to cope with the demands of the trade. There are so many resources and avenues for teachers out there to be able to go beyond the norm of the profession. With the nature of training many new teachers are exposed to, there are so many things that they can do to help their learners. Yet, when asked if they had been able to go beyond the norm of the profession, many confessed that they do not usually have the time needed to seek out, read and organise information so as to be able to practice more than what is stated in the textbook or even the syllabus. This paper will explain the effort taken by the Education Faculty of Universiti Teknologi Malaysia in instilling collaboration amongst its teacher- trainees in building a material databank by the teacher-trainees and for the teacher-trainees.